If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 5(x + -9) Reorder the terms: 6 + 5x = 5(x + -9) Reorder the terms: 6 + 5x = 5(-9 + x) 6 + 5x = (-9 * 5 + x * 5) 6 + 5x = (-45 + 5x) Add '-5x' to each side of the equation. 6 + 5x + -5x = -45 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + 0 = -45 + 5x + -5x 6 = -45 + 5x + -5x Combine like terms: 5x + -5x = 0 6 = -45 + 0 6 = -45 Solving 6 = -45 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x/3-(3x-7)/5=(x-2)/6 | | 3.2+x=3.4 | | 60/400 | | (56x^2-8x^3)/(x^2(7-x)) | | 5m+1=m^2-49 | | -2(5)+y=1 | | f(x)=2x^2-8x-10 | | 18=k(28) | | 140=30+5s | | 19=a-5.4 | | 3x^2+20x=-12 | | 16=2w+(-8)+10w-12 | | 9(12)+9(3)= | | 50+10x=15+15x | | 4+19m-2=6m+104-4m | | -4/7(y-21)-1/14y= | | 1.875w=11.25 | | X+8=y+7 | | 3x-4-x=8 | | 32n=4 | | 3.4t=13.6 | | 5b=21+b | | -k+5=5k-1 | | 8x+3y=-18 | | 3x+84=336 | | 5b=21+4n | | 4t+16-3= | | 3x+84+90=180 | | -17=0.2n-20 | | 3x+84=156 | | x-34=47 | | -6.1(3s+6)-2.8(2s-4)= |